PENDIDIKAN ISLAM SYEKH YUSUF - M. Asep Rahmatullah; Aslihatul Rahmawati; Neni Nuraeni (Cakrawala Pedagogik, 2025)
The word of Islamic education today is experiencing a identity, morality dan multidimensional ciris of, encompassing both the curriculum system and the quality of teaching staff, as well as the availability of infrastructure. This has resulted in a liberalistic, materialistic, capitalistic, and secularistic education system that has lost its true purpose. The first Islamic education was carried out by the Prophet Muhammad SAW in Mecca and Sheikh Yusuf Al-Maqasari who was once an Islamic education teacher and Islamic law judge during the reign Of Sultan Ageng Tirtayasa Banten. This study employed qualitative methods based on a literature review, drawing on books, Google Scholar, and other sources. The results suggest. That Islamic education must return to its sources, the Quran dan the Sunnah. The First concept of Islamic education is the education of faith and belief, the second is the concept of sharia in Islam, and the third is the formation of moral character.